Fundamentals of case study research in family medicine and community health - Fàbregues, Sergi (Fam Med Community Health, 2019)
The aim of this article is to introduce family medicine researchers to case study research, a rigorous research methodology commonly used in the social and health sciences and only distantly related to clinical case reports. The article begins with an overview of case study in the social and health sciences, including its definition, potential applications, historical background and core features. This is followed by a 10-step description of the process of conducting a case study project illustrated using a case study conducted about a teaching programme executed to teach international family medicine resident learners sensitive examination skills. Steps for conducting a case study include (1) conducting a literature review; (2) formulating the research questions; (3) ensuring that a case study is appropriate; (4) determining the type of case study design; (5) defining boundaries of the case(s) and selecting the case(s); (6) preparing for data collection; (7) collecting and organising the data; (8) analysing the data; (9) writing the case study report; and (10) appraising the quality. Case study research is a highly flexible and powerful research tool available to family medicine researchers for a variety of applications.